Influence of the Environment on Participation in Social Roles for Young Adults with Down Syndrome - Foley, K.; Girdler, Sonya; Bourke, J.; Jacoby, P.; Llewellyn, G.; Einfeld, S.; Tonge, B.; Parmenter, T.; Leonard, H. (PLOS, 2014)
Background: The concept of disability is now understood as a result of the interaction between the individual, features related to impairment, and the physical and social environment. It is important to understand these environmental influences and how they affect social participation. The purpose of this study is to describe the social participation of young adults with Down syndrome and examine its relationship with the physical and social environment. Methods: Families ascertained from the Down syndrome ‘Needs Opinion Wishes’ database completed questionnaires during 2011. The questionnaires contained two parts, young person characteristics and family characteristics. Young adults’ social participation was measured using the Assessment of Life Habits (LIFE-H) and the influences of environmental factors were measured by the Measure of the Quality of the Environment (MQE). The analysis involved descriptive statistics and linear and logistic regression. Results: Overall, participation in daily activities was higher (mean 6.45) than in social roles (mean 5.17) (range 0 to 9). When the physical and/or social environment was reported as a facilitator, compared to being no influence or a barrier, participation in social roles was greater (coef 0.89, 95%CI 0.28, 1.52, coef 0.83, 95%CI 0.17, 1.49, respectively). The relationships between participation and both the physical (coef 0.60, 95% CI -0.40, 1.24) and social (coef 0.20, 95%CI -0.47, 0.87) environments were reduced when age, gender, behavior and functioning in ADL were taken into account. Conclusion: We found that young adults’ participation in social roles was influenced more by the physical environment than by the social environment, providing a potentially modifiable avenue for intervention.